Bone-tissue engineering: complex tunable structural and biological responses to injury, drug delivery, and cell-based therapies. (2nd October 2015) - Alghazali, Karrer M.; Nima, Zeid A.; Hamzah, Rabab N.; Dhar, Madhu S.; Anderson, David E.; Biris, Alexandru S.
Abstract: Bone loss and failure of proper bone healing continues to be a significant medical condition in need of solutions that can be implemented successfully both in human and veterinary medicine. This is particularly true when large segmental defects are present, the bone has failed to return to normal form or function, or the healing process is extremely prolonged. Given the inherent complexity of bone tissue – its unique structural, mechanical, and compositional properties, as well as its ability to support various cells – it is difficult to find ideal candidate materials that could be used as the foundation for tissue regeneration from technological platforms. Recently, important developments have been made in the implementation of complex structures built both at the macro- and the nano-level that have been shown to positively impact bone formation and to have the ability to deliver active biological molecules (drugs, growth factors, proteins, cells) for controlled tissue regeneration and the prevention of infection. These materials are diverse, ranging from polymers to ceramics and various composites. This review presents developments in this area with a focus on the role of scaffold structure and chemistry on the biologic processes that influence bone physiology and regeneration.